EFFECTIVENESS OF GROUP COUNSELING SERVICES USING MOTIVATIONAL INTERVIEWING TECHNIQUE TO IMPROVE GRIT IN FINAL SEMESTER STUDENTS: Final Year Students, Grit, Group Counseling, Motivational Interviewing - Nur Jihan Maimanah; Nefi Darmayanti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to determine the effectiveness of group counseling services using the Motivational Interviewing technique in increasing grit among final-year students. The research employed a quantitative approach with a pre-experimental method using a One Group Pretest-Posttest design. The participants consisted of 8 eighth-semester BKPI-2 students who were selected based on low grit levels and their willingness to participate in group counseling. The data collection instrument used a grit scale that measured two main aspects: perseverance and consistency of interest. The analysis results showed a significant increase in grit scores before and after the intervention, as evidenced by the Wilcoxon Signed Rank Test (sig. value = 0.012 < 0.05). Thus, group counseling services using the Motivational Interviewing technique proved to be effective in enhancing grit among final-year students.